Discovering Matthew Content, Interpretation, Reception - Boxall, Ian 1964- (Chicago Wm. B. Eerdmans Publishing Co., 2015)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- Acknowledgements -- List of Abbreviations -- 1 Introduction -- 2 Interpreting Matthew: Strategies for Reading -- 3 The Text of Matthew: Puzzles and Possibilities -- 4 Characters and Places in Matthew's Story -- 5 Matthew's World: Locating the Text Historically and Socially -- 6 Beginnings: The Infancy Narratives -- 7 Jesus as Teacher: Ethics and Judgement -- 8 Jesus as Healer and Exorcist -- 9 Fulfilling the Law and the Prophets -- 10 'Built upon the Rock': The Gospel of the Church -- 11 Endings: The Passion and Death of Jesus -- 12 Endings and New Beginnings: The Resurrection of Jesus -- 13 Conclusions: Interpreting Matthew Today -- Bibliography -- Index of Biblical References -- Index of Ancient Texts -- Index of Names and Subjects.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books